Onset of puberty: Mother knows best - Biro, Frank M. (J Pediatr Adolesc Gynecol, 2020)
BACKGROUND: Several strategies have been proposed to determine onset of puberty without examination by a trained professional. This study sought to evaluate a novel approach to determine onset of puberty in girls. METHODS: This study utilized the Cincinnati cohort of the Breast Cancer and the Environment Research Program. Girls were recruited at 6–7 years of age and followed every six months in the initial six years, and annually thereafter. Breast maturation and foot length were performed at each visit by health professionals certified in those methods. Mothers were asked to provide the age that they believed their daughter’s shoe size increased more rapidly. RESULTS: These analyses include 252 participants. Age at increase in shoe size was correlated to age at onset of puberty (r=.21) and increase in foot length (r=.24). The difference of reported age of increased shoe size was 0.46 years before breast development. CONCLUSIONS: Reported increase in shoe size occurred somewhat earlier and was significantly correlated to age of breast development. These preliminary results suggest that mother’s report of increase in shoe size appear to be as accurate as reports of other indirect methods of determining onset of puberty, such as self- or maternal estimates of breast development.